A Kantian Theory of Employment, or How Domestic Right Structures Contemporary Work: A Reply to Williams - Pascoe, Jordan (Con-Textos Kantianos. International Journal of Philosophy, 2024)
This article shows how Kant’s framework of domestic right can be understood as a model for modern employment law, a suggestion made by Garrath Williams in a commentary on Kant’s Theory of Labour. I begin by exploring how Kant’s historical context informed his account of labor relations and argue that he made three key innovations: the theorization of domestic right, the linkage of work and political standing, and the development of contract right to make sense of the material dependency and formal equality of “free” contract workers. This account of contract-based work, however, sketches a dangerous “fantasy” of free contract that we see echoed in contemporary defenses of the gig economy. I show that this argument is central to understanding Kant’s evolving conception of the relationship between labor and citizenship, but I defend the claim that modern employment resembles domestic right more closely than contract right, by attending to both the formal structures of modern employment law and the lived experiences of professional employment in the digital age. Finally, I explore how drawing on the domestic model for understanding modern employment can help us to see the limits of both Kantian and contemporary accounts of the public good, by highlighting the ways that public law is deployed to formalize asymmetrical relations of dependence, to check their capacity for exploitation and domination. In so doing, public law acts to limit the scope of the state’s responsibility for both the formal and material conditions of equality, freedom, and flourishing, enforcing conditions in which citizens must rely on private employers for goods like health insurance, sick leave, and a minimum income.